PENGARUH PERILAKU KEPEMIMPINAN, IKLIM ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA DOSEN DI UNIVERSITAS SLAMET RIYADI SURAKARTA - Fauzi, Annas; Aris Tri Haryanto, Winarti, (Solidaritas, 2017)
PENGARUH PERILAKU KEPEMIMPINAN, IKLIM ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA DOSENDI UNIVERSITAS SLAMET RIYADI SURAKARTA Oleh:Annas Fauzi, Dr. Winarti, M.Si.,Drs. Aris Tri Haryanto, M.Si. ABSTRACT This study aims to determine: (1) The effect of leadership behavior on lecturers performance at Slamet Riyadi University; (2) The effect of organizational climate on the performance of lecturers at Slamet Riyadi University; (3) the effect of work motivation on lecturers performance at Slamet Riyadi University; (4) The effect of leadership behavior, organizational climate and work motivation simultaneously on lecturers performance at Slamet Riyadi University. This research uses quantitative approach with survey method. The research subjects are all lecturers at Slamet Riyadi University Surakarta with a population of 120 lecturers. Sampling technique using Proportionate Stratified Random Sampling. The number of samples used amounted to 60 lecturers. Data collection techniques that used are questionnaires. Furthermore, the test instrument used the test validity and reliability test. Test prerequisite analysis used normality data test, linearity test, multicollinearity test. Then test the hypothesis using multiple regression. The results showed; (1) there was a positive and significant effect between leadership behavior on lecturer performance at Slamet Riyadi University with effective contribution of 8,07%; (2) there is a positive and significant influence between organizational climate on lecturers performance at Slamet Riyadi University of 14.02%; (3) there was a positive and significant effect between work motivation on lecturer performance at Slamet Riyadi University of 13.21%. (4) there were positive and significant effect between leadership behavior, organizational climate and work motivation simultaneously to lecturer performance at Slamet Riyadi University equal to 35,30%. Keywords: Leadership behavior, organizational climate, work motivation, lecturer performance of Slamet Riyadi University.